Direct evidence for local IgE production in the human colonic mucosa - Canziani, Karina Eva (2020)
Understanding the biology of IgE in humans has become a matter of interest that remains incompletely understood due to the rarity of peripheral IgE+ cells. The increased incidence of allergic diseases and food-induced anaphylaxis overtime demands an urgent development of disease-modifying therapies that reverse the synthesis of IgE and the induction of IgE-mediated allergic reactions. Although some reports showed specific IgE in stools and IgE+ cells in the gastrointestinal tract of allergic patients,1, 2 the microanatomical location of the class-switch recombination (CSR) to ε chain is largely unknown. This isotype is produced through CSR mechanism by activated IgM-producing B cells (direct switch) or following IgG+ B memory cell-switch to ε chain (sequential switch) in a Th2 milieu with the induction of the cytidine deaminase (AID).3 It has been demonstrated that this mechanism occurs prior to germinal center (GC) formation in secondary lymphoid tissues such as lymph nodes and tonsils,4 but it is controversial whether the IgE isotype switching can occur in the human intestinal mucosa and which niches could be involved. Our study aimed to investigate the local IgE synthesis in the stroma of juvenile colonic polyps (JP) from patients with rectal bleeding and the relationship between IgE production and food sensitization, a risk factor for food allergy.